Promotion Costs Analysis To Increased Volume Sales In The Convection Companies - Listiawati; Karta Negara Salam; Retno Wulansari; Pramudi Harsono (International Journal of Science, Technology & Management, 2021)
The purpose of this study is to obtain empirical data about whether or not there is a relationship between sales promotion costs and sales volume and how much influence the promotion costs have on sales volume at the company. In this study, the documentation method was used in data collection, then proceeded to the analysis process using correlation and regression analysis.The population in this study is the total cost of sales promotion and sales volume at the company. Due to the limitations of time, cost, manpower, and so on, the researchers took samples, namely sales promotion costs, and company sales volume, between 2018-2020.Based on the results of the analysis for three years, it was obtained that r XY = 0.718 with N = 36 and a significant level of 0.000, obtained r table = 0.708. This shows r xy> r table, which means that r XY is significant and Ha is accepted. Because Ha is accepted, there is a positive and significant relationship between Sales Promotion Costs and Sales volume at convection companies. Furthermore, the influence of Biya promotion on sales volume can be seen on the determinant coefficient (R 2) where it is mentioned in a row in 2018; 2019; and 2020 is 0.675; 0.554; and 0.507. this shows that the average annual promotion costs have an effect of more than 50% on the company's sales volume.